MANFAAT ALOKASI DANA DESA BAGI MASYARAKAT DESA (Studi Pada Desa Blankahan Kecamatan Kuala Kabupaten Langkat) - Misno UMA (Universitas Medan Area, 2016)
Authority possessed through the village to take care of and organize their peoples then becomes imperative that the village through village pemrintah need a budget in the implementation of the authority in the village, ni Research aims to see manfaatalokas village funds (ADD) for the people of the District of Kuala KapatenLankat Blankahan village. The research method used is by using smber manifold qualitative data through interviews and documentation. From research conducted in the know that the village fund allocation (ADD) derived from financial balance of central and local government are present at very affects the growth rate of each village. Similarly with the village Blankahan with ADD is now the village Blankahan greatly helped in carrying out rural development in stages in order to realize the welfare of society. On the other hand related to the presence of ADD, the village administration Blankahan need to improve knowledge of the village administration in managing the human resources and financial use ADD as expected from the legislation in force.